EFEK ANTIPIRETIK EKSTRAK DAUN CABE RAWIT (Capsicum annum L) TERHADAP TIKUS PUTIH JANTAN (Rattus norvegicus) YANG DIINDUKSI VAKSIN Difteri Pertusis Tetanus - Inggrid Yuliana; Yuliet Yuliet; Khildah Khaerati (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Leaves cayenne pepper (Capsicum annuum L) is a plant that empirically has been used as a fever-lowering. This study aims to determine the effect of the antipyretic effect of leaf extract of cayenne pepper and determine the effective dose as an antipyretic. Tests carried out using fever inducers ie vaccine DPT (Diphtheria Tetanus Pertussis) 0.2 ml. Tests the antipyretic effect is divided into six treatment groups. The first group was given Na-CMC 1% as the normal control group were given a 2nd Na-CMC and DPT vaccine induced a 0.2 ml as a negative control group all 3 were given paracetamol as a positive control, a group of 4th, 5th and all six were given the leaf extract of cayenne pepper with a dose of 100 mg/kg BW, 200 mg/kg BW, and 300 mg/kg BW. Rectal temperature measurement is carried out for 6 hours with intervals of 30 minutes. Temperature measurement data were statistically analyzed using oneway ANOVA test. Antipyretic activity test results showed that the leaf extract of cayenne pepper has antipyretic activity in male rats and the dose that effectively lower rectal temperature of rat is 300 mg/kg BW.